Veterinary Bacterial Zoonoses - Jiabo Ding; Shengqing Yu; Xin Ting; Menachem Banai (Frontiers Media SA, 2021)
Humans, animals and microorganisms all share the same planet, the last playing critical roles in the cycling of nitrogen and sulfur in nature and the degradation of organic materials. Unfortunately, micro-organismal populations also include infectious bacteria and viruses that cause diseases, with a few that have fatal consequences. We chose veterinary bacterial zoonoses as our Research Topic with the aim of delivering up-to-date scientific knowledge on the subject, addressing the topics of detection approaches, vaccine development and host immune response. Our Research Topic alludes to the One Health approach in addressing three important bacterial diseases, Brucella, Mycobacteria and Chlamydia. A short chapter also elaborates on a highly pathogenic field isolate of Mycobacterium avium spp. Avium and an atypical enteropathogenic Escherichia coli O98 as evolving zoonotic risks. The cover illustration is intended to raise our awareness of the fact that pets play a role in our life as passionate and compassionate friends, but that they also pose a health risk due to carrying a bacterial or a viral zoonotic agent. We hope our Research Topic will further the pursuit of these topics and spark research in other important diseases.